Does Delivery Model Matter? The Influence of Course Delivery Model on Teacher Candidates’ Self-Efficacy Beliefs Towards Inclusive Practices - Smothers, Moriah; Colson, Tori; Keown, Stacey (International Review of Research in Open and Distributed Learning, 2020)
A causal-comparative research design was used to examine the influence of course delivery (face-to-face flipped or asynchronous online) on participants’ self-efficacy beliefs toward teaching in an inclusive classroom. The following research questions were used to guide the study: (a) Is there a relationship between completing an introduction of exceptionalities course and participants’ self-efficacy toward teaching an inclusive classroom? (b) Is there a relationship between completing an introduction of exceptionalities course in an asynchronous online or face-to-face flipped format on participants’ self-efficacy beliefs toward teaching in an inclusive classroom? The purpose of this study was to explore if there is a relationship between self-efficacy belief development and course delivery models. The results indicated a significant difference in self-efficacy beliefs towards teaching in an inclusive classroom after completing an introduction of exceptionalities course. However, there was no significant difference in the participants’ efficacy based on the course delivery model (face-to-face flipped or asynchronous online). Implications and suggestions for future research are discussed.